Pentingnya Filsafat Bagi Ilmu Pendidikan Agama Kristen - Reyna Nurani Siregar Lete; Mozes Lawalata (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2024)
Philosophy is a method of thinking systematically and critically. In relation to Christian religious education, it must be studied systematically and critically as a basic science so that it can be on par with other sciences that show real benefits for the development of humanity. The author will describe Christian Religious Education as an ontological, epistemological and axiological practice of science. The method used in this research is a literature study approach. Ontologically, Christian religious education must be a strong guide towards the journey of human life so that he is able to exist and exist both theologically and socially. Epistemology talks about knowledge. Epistemologically, the Bible and Jesus are sources of epistemology for Christian religious education. Axiology talks about utility value. The axiological foundation of Christian religious education is a loving humanism that is imbued with Christian values. In other words, axiology can help humanize humans and liberate them from the alienation of their human function in life.